Teachers’ Perceptions of Technological Knowledge in English Language Teaching Practices - Nila Irmayani; Chairil Anwar Korompot; Fitriyani (Universitas Islam Negeri Palopo, 2026)
This study explores English teachers’ perceptions of technological knowledge in teaching English within the TPACK framework. Teachers’ perceptions play an important role in determining how technology is selected and integrated into classroom instruction to support effective learning. This research employed a qualitative approach with a narrative inquiry design. The participants were English teachers at a junior high school in Mangkoso. Data were collected through interviews and classroom observations to capture teachers’ experiences in using technology during the teaching process. The findings reveal that teachers have positive perceptions of technological knowledge, as they demonstrate confidence in operating various digital tools and integrating them into instructional activities to support student engagement and learning. However, the study also identifies several challenges related to teachers’ digital skills, indicating the need for continuous professional development.